Monitoring and planning of local territorial development as a modelable business process: the case of Latvian municipalities - Vera Komarova; Edmunds Cizo; Timurs Boronenko (Vestnik of Vitebsk State Technological University)
The relevance of the study is driven by the need to improve the efficiency of monitoring and planning processes for local territorial development, which are currently unstructured and insufficiently systematized in Latvian municipalities. With the growing demand for transparency and effectiveness in municipal governance, the application of business process modeling (BPMdl) tools is a pressing issue.